Latihan Dasar Kepemimpinan dalam Organisasi Siswa Intra Sekolah (OSIS) SMP Negeri Kabupaten Deli Serdang - Syahputra, Muhammad Rizki; Saputra, Anri; Thahir, Jamilah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IAIN Lhokseumawe, 2023)
This study aims to describe the steps of implementing basic leadership training activities for Intra-School Student Organizations (OSIS) in State Junior High Schools in Deli Serdang Regency. The research method used is qualitative by prioritizing the process of interaction and in-depth communication between the researcher and the phenomenon under study. Data were collected through observations and interviews with student council advisors, student council administrators, and students. The steps of basic leadership training were designed by considering determining training objectives, planning training materials, group involvement, instilling leadership values and ethics, effective communication training, involving student council leaders as mentoring, and encouraging student council leaders to be positive examples. The results showed that the basic leadership training by the student council had a positive impact in shaping students' characters, including increased self-confidence, creativity, initiative, and responsibility. Positive responses from the school principal, teachers, student council leaders and students indicated the success of the training. Requests for ongoing activities confirmed the desire to continue student leadership development efforts. The recommendation of this study is that coaching and strengthening the role of the student council as an agent of student leadership formation needs to continue to be considered so that the positive characteristics that have been formed can be maintained and improved.